Pengaruh Mental Imajeri terhadap Ketangguhan Mental dan Performa Olahraga Atlet: Tinjauan Bibliometrik - Khuluqin Azhiim, Agita Naufal; Muluk, Hamdi; Guritna, Taru (JSKK (Jurnal Sains Keolahragaan dan Kesehatan), 2026)
This study aims to systematically map the development of research on mental imagery in relation to athletes’ mental toughness and sports performance using a bibliometric approach. Data were obtained from the Scopus database, resulting in 183 journal articles published between 1977 and 2025. The analysis includes publication trends, citation structures, journal productivity, and keyword co-occurrence mapping using VOSviewer and RStudio.The results show a substantial increase in research output after 2010, with more than 40% of total publications produced after 2020, and a peak in 2023 with 17 articles. Citation analysis indicates that a limited number of highly cited studies dominate the field, reflecting a concentrated pattern of scientific influence. Keyword co-occurrence analysis identifies mental imagery as a central construct linking performance enhancement, psychological regulation, and injury rehabilitation, with four main thematic clusters. This study addresses the fragmented nature of previous research by providing an integrated bibliometric mapping of mental imagery studies across performance and psychological domains. The main contribution lies in identifying research trends, intellectual structures, and emerging directions, particularly in technology-based interventions and longitudinal approaches in sport psychology.